The Relationship Between Peer Groups and the Learning Independence of Biology Education Students - Astina Astina; Wendy Renae Johnson (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the relationship between peer groups and the learning independence of biology education students. Methodology: This type of research is quantitative with a correlation method. The population of this study was Biology Education Students, totaling 263 people with a sample size of 132 people. Sampling was carried out using Simple Random Sampling. The data collection techniques used are the learning independence scale and the peer group scale. The data analysis technique is descriptive statistical analysis and inferential statistical analysis with product moment correlation techniques. Main Findings: The research results based on descriptive statistical analysis show that independence in learning is in the low category with an average value of 88.56 and the peer group is in the medium category with an average value of 87. Meanwhile, the results of inferential statistical analysis show that rcount is greater than rtable or 0.27 ≥ 0.24, H0 is rejected and H1 is accepted, meaning that there is a relationship between the peer group and the learning independence of students. Where is the sig value. 2-tailed is 0.00 ≤ 0.05. Novelty/Originality of this study: This research contributes to explaining the social aspects of independent learning that are often overlooked in previous literature. While much research has explored internal factors that influence learning independence, the emphasis on the role of peer groups as external agents influencing students' motivation, mindset, and learning styles, is an innovative focus point. This enriches our insight into how social interaction with fellow students can have a significant influence on the level of learning independence of Biology Education students.